Evaluation of New Seismic provisions for special concentrically braced frames in AISC 341-22 - Shen, Jay; Şeker, Onur; Faytarouni, Mahmoud; Akbaş, Bülent; Zhang, Hanming; Li, Peizhe (Elsevier Science Inc, 2024)
The seismic provisions for special concentrically braced frame (SCBF) had expected the properly detailed braces to provide inelastic cyclic deformation of 10 - 20 ductility without fracture during the design earthquake ground motions over 30 years prior to 2022. The new seismic provisions for SCBF in AISC 341-22 eliminates the clear and quantifiable statements on the expected capacity and demand of the braces, and indicates that the diagonal braces can sustain large inelastic cyclic deformations without experiencing premature failures if they are properly detailed for ductility as prescribed in the provisions. The appearance of such word as large inelastic deformation and premature failure causes a concern about the uncertainty. One might wonder why a range of amount of inelastic cyclic deformation capacity for a properly detailed brace cannot be defined after more than 40 years of extensive research on SCBF. This paper presents a study using available data accumulated over more than 40 years to investigate how much inelastic cyclic deformations are needed for braces to avoid fracture under the design earthquake, and concludes that the SCBFs with properly detailed square HSS have insufficient inelastic cyclic deformations to avoid experiencing premature failures that lead to structural collapse under the design earthquake.
Keywords: Seismic design; Special braced frame; Brace fracture; Earthquake hazard